The impact of electronic payments on theft - ahmad salahmanesh; seyed aziz arman; vahid kafili; ahmad dehghani (پژوهش‌های برنامه و توسعه)
Purpose: One of the important developments in the payment system is the emergence of new payment tools known as electronic payment instruments. With the help of electronic payment tools, the possibility of earning money by stealing is reduced; Thus reducing the amount of theft is a predicted resultof increased access to electronic payment instruments. In this research, this hypothesis has been investigated for the period between 1386- 1394 using data from Iran's provinces. Methodology: Panel GMM method is used to estimate the regression equation. Results: The results show that the expansion of electronic payment tools in Iranian provinces has had a negative effect on theft. Also, the rate of urbanization, the misery index (sum of the unemployment rate and inflation rate), industrialization and income inequality have had a positive impact on theft. Accordingly, some policy suggestions have been offered to extend the use of these tools.Keywords: Iran, Thief, Panel data Electronic Payment, GMMJEL Classification: K19, E42, C33